Effects of Consecutive Versus Non-consecutive Days of Resistance Training on Strength, Body Composition, and Red Blood Cells - Yang, Yifan; Bay, Pang B.; Wang, Yongtai R.; Huang, Junli; Teo, Hilary W. J.; Goh, Jorming (Frontiers in Physiology, 2018)
Health authorities worldwide recommend 2-3 days per week of resistance training (RT) performed 48-72 h apart. However, the influence of recovery period between RT sessions on muscle strength, body composition and red blood cells (RBCs) are unclear. Aim: Examine the effects of three consecutive (C) or nonconsecutive (NC) days of RT per week for 12 weeks on strength, body composition and RBCs. Methods: Thirty young, healthy and recreationally active males were randomly assigned to 3 C ( 24 h between sessions) or NC ( 48-72 h between sessions) days of RT per week for 12 weeks. Both groups performed 3 sets of 10 repetitions at 10-repetition maximum (RM) of leg press, latissimus pulldown, leg curl, shoulder press and leg extension for each session. Ten RM and body composition were assessed pre- and post-RT. RBC parameters were measured on the first session before RT, and 0 and 24 h post-3rd session in untrained (week 1) and trained (week 12) states. Results: No training x group interaction was found for all strength and body composition parameters (p = 0.075-0.974). Training increased strength for all exercises, bone mineral density, and total body mass via increased lean and bone mass (p < 0.001). There was no interaction (p = 0.076-0.994) and RT induced temporal changes in all RBC parameters (p < 0.001-0.003) except RBC corrected for plasma volume changes (time x training interaction; p = 0.001). Training increased hematocrit and lowered mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration (p = 0.001-0.041) but did not alter uncorrected RBC, hemoglobin, mean corpuscular volume and RBC distribution width (p = 0.178-0.797). Conclusion: Both C and NC RT induced similar improvements in strength and body composition, and changes in RBC parameters.